PENGARUH BALAI LATIHAN KERJA TERHADAP KUALITAS TENAGA KERJA DI KABUPATEN DHARMASRAYA DALAM PERSPEKTIF EKONOMI ISLAM - Delli Puspita; Rusydi Fauzan (CV. Adiba Aisha Amira, 2024)
The purpose of this study is to find out whether and to what extent Vocational Training Center affects the quality of workforce in Dharmasraya Regency Vocational Training Centre. This study can be further used to improve the quality of the workforce. The type of research used in this work is a quantitative descriptive research with a quantitative approach and a field study with questionnaires (Likert scale), and the total sample of the study was 92 respondents. The data analysis method uses validity, reliability, classic assumptions (normality test, autocorrelation test), simple linear regression test, hypothesis test (t-test) and R² determination test. The results of this study show that the value of the regression coefficient is 0.107, when increasing each cost variable by one unit affects the quality of work by 0.107. Then calculated t value = 0.765 which is less than t table = 1.98667 (0.765 andlt; 1.98667) and sig is 0.00 andlt; 0.05. This indicates that H1 is accepted or H0 is rejected. And the R² test results got a value of 0.006 or 0.06%. Which proves that the independent variable can explain 0.06% of the dependent variable and the remaining 0.94%. Based on the t-test, job training centers have a partially significant effect on the quality of work in Dharmasraya Regency.